An analysis of the European integration processes in Ukraine - Semenets, А.; Tiurina, D.; Kuzkin, Ye.; Yarmak, O. (ТОВ "Фінтехальянс", 2020)
The purpose of the article is to analyze the efficiency of cooperation between Ukraine and the European Union, in general and expediency of Ukraine’s joining the Free Trade Area, in particular, as well as to prove the expediency of European integration processes, in general. The article deals with the history of the development of Ukraine’s integration into the European Economic Community. The main expectations, risks and results of measures aimed at integrating the Ukrainian economy into the European one are considered. Two main viewpoints on the results of the European integration are revealed. The first one is that the European integration is a blessing in all respects, it has no obvious and significant risks and should bring economic and social prosperity to Ukraine, promote Ukraine’s transition to the European social standards, due to economic growth caused by expanding target markets for Ukrainian products (giving access to the capacious European market), guarantee rapid growth of direct foreign investment in the Ukrainian economy, the improvement of the export-import balance, the creation of new jobs, the intensification of innovation processes and an increase in tax revenues to the budgets at all levels, the revamping of Ukrainian industry and the entire economy. The second viewpoint is quite opposite to the first one. It says that the European integration will cause deindustrialization, accompanied by a massive reduction of jobs; emigration of a significant and most capable part of the population; and as a consequence, acute shortage of labor resources, catastrophic increase in social tension and Ukraine’s transformation into Europe’s raw material appendage. Research carried out in the field of investment activity confirms the collapse of direct foreign investment in the Ukrainian economy during the period of the EU integration. Currently, foreign investors, at best, take a wait-and-see attitude, waiting to see the direction in which Ukraine’s political, economic and social development will go. The state of the trade-economic balance with the EU has deteriorated noticeably, as well as the state of the labor market and innovation activity. The research carried out clearly confirms the validity of the second viewpoint. Further studies of integration processes should be aimed at a significant modification of the goals and directions of Ukraine’s European integration, and should help Ukrainians to find a way out of the socio-economic crisis and rank high in the global division of labor.

Метою статті є дослідження ефективності співпраці України з Євросоюзом у цілому і доцільності входження нашої країни до Зони вільної торгівлі зокрема, а також обґрунтування доцільності реалізації євроінтеграційних процесів взагалі. Розглянуто історію розвитку інтеграційних процесів України до Європейського економічного співтовариства; основні очікування, ризики і результати заходів, спрямованих на інтеграцію української економіки в європейську. Виявлено дві основні позиції на результати євроінтеграції для України. Перша полягає в тому, що євроінтеграція для України є благом в усіх аспектах, без очевидних та істотних ризиків, і повинна принести Україні економічне і соціальне процвітання, сприяти переходу України на європейські соціальні стандарти, на підставі економічного зростання за рахунок розширення ринків збуту української продукції (вихід на ємний європейський ринок), стрімкого зростання обсягів прямих іноземних інвестицій в українську економіку, поліпшення стану експортно-імпортного сальдо, створення нових робочих місць, активізації інноваційної діяльності та збільшення податкових надходжень до бюджетів усіх рівнів, перехід промисловості України і всієї економіки в цілому на новітні технології. Друга — діаметрально протилежна. І полягає в тому, що євроінтеграція України призведе до того, що відбудеться деіндустріалізація України, супроводжувана масовим скороченням робочих місць, еміграцією значної і найбільш працездатної частини населення і як наслідок — найгостріший дефіцит трудових ресурсів, катастрофічне зростання соціальної напруженості і перетворення України на сировинний придаток Європи. Проведені дослідження в царині інвестиційної діяльності підтверджують обвальне падіння обсягів прямих іноземних інвестицій в економіку України за період інтеграції в ЄС. У даний час іноземні інвестори в кращому разі займають вичікувальну позицію, вивчаючи, в якому напрямі піде розвиток України в політичному, економічному та соціальному аспектах. Помітно погіршилися стан торговельно-економічного сальдо, причому саме з ЄС, стан ринку праці та інноваційної діяльності. Проведені дослідження підтверджують з усією очевидністю правоту другої позиції. Подальші дослідження інтеграційних процесів повинні бути спрямовані на істотне коригування цілей і напрямів євроінтеграції України і сприяти виходу із соціально-економічної кризи і гідного місця у світовому розподілі праці.
Аналіз розвитку євроінтеграційних процесів в Україні
Keywords: economic crisis; enterprise; European integration; export; import; industry; investment; євроінтеграція; інвестиції; експорт; імпорт; економічна криза; підприємство; промисловість